The lipoprotein abnormality in Tangier disease: quantitation of A apoproteins. - Assmann, G (1977)
In this study we have determined by radioimmunoassay and double immunoelectrophoresis the total quantities and distributions of A apoproteins in three adult patients affected with Tangier disease (hereditary alpha-lipoprotein deficiency). Compared with normal plasma, the total quantities of apoproteins A-I and A-II in Tangier plasma were determined to be less than 1% and 5-7%, respectively. In Tangier patients, approximately 90% of the apoprotein A-I sedimented when ultracentrifugations of plasma were carried out at density 1.21 g/ml KBr. By contrast, more than 95% of the apoprotein A-II floated under those conditions. In normal plasma, approximately 90% of both apoproteins A-I and A-II is found in the 1.063-1.21-g/ml KBr density fraction. These findings suggest that complete dissociation of A apoproteins occurs in Tangier plasma. This dissociation of apoproteins was confirmed by double immunoelectrophoresis with monospecific antisera. Immunochemical and electrophoretic experiments did not provide evidence for a structural abnormality of apoprotein A-I in these patients, The results taken together strongly suggest that normal high-density lipoproteins are absent from Tangier plasma.